(untitled) (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2022)
The article presents an analysis of blockchain technology. Blockchain is the best tool of the current decade. The possibility of using this innovative technology to ensure information security is shown. Blockchain technology was created to store transaction data. However, the structure of block chains using blockchain technology allows you to store various other metadata – catalogs, registries, directories, metadata databases, etc. This makes it possible to use blockchain technology for backup, information protection. The use of blockchain technology can provide complete decentralization of domain names and distribution of content across a larger number of nodes, which will make it virtually invulnerable to cyber attacks The article identifies the technological aspects of the introduction of Blockchain technology, substantiates the main characteristics of this technology, and notes the accepted typology of Blockchain varieties depending on the specifics of implementation and technological features. There are varieties of algorithms for "consensus" agreements, both in the context of technologies.